Development of Sales Strategy Through Social Media and Marketplace to Increase Sales of PT Alkhafi Supply Chain: Pengembangan Strategi Penjualan Melalui Media Sosial dan Marketplace Untuk Meningkatkan Penjualan PT Alkhafi Supply Chain - AGUS ARI SUSANTO; Andry Rahmadhany Rahmadhany (Procedia of Social Sciences and Humanities, 2026)
General Background: The rapid growth of internet penetration and digital technology has transformed global consumer behavior, positioning e-commerce as a fundamental component of modern retail transactions. Specific Background: PT Alkhafi Supply Chain, a distributor of imported goods, utilizes social commerce platforms like TikTok and traditional marketplaces such as Shopee to establish new brands and navigate intense market competition. Knowledge Gap: Despite the widespread adoption of online selling, many distributors struggle to achieve consistent sales conversions organically without relying heavily on paid advertising while facing severe price competition from established players. Aims: This research determines the application of organic marketing strategies within social media and marketplaces to drive sales volume for imported product distributors. Results: Descriptive qualitative analysis reveals that TikTok enables rapid market penetration through content-driven impulse purchases, whereas Shopee involves extensive price comparisons resulting in lower initial conversion rates. The strategic use of data analytics tools for product research, specifically targeting high-demand items like motoric toys and portable fans, proved vital for competitive inventory selection. Novelty: This study highlights the contrasting consumer purchasing behaviors between content-integrated social commerce and traditional marketplaces when deploying organic, zero-ad expenditure strategies for newly launched distributor brands. Implications: Businesses must prioritize rigorous competitor analysis, high-quality visual content, and consistent store decoration to thrive organically in digital marketplaces, adapting their approach based on platform-specific consumer habits. Highlights: TikTok's integrated video and shopping features facilitate rapid market penetration through content-driven impulse purchasing. Shopee users exhibit highly analytical buying behaviors by prioritizing price comparisons and store performance metrics. Data analytics tools for competitor and product research remain crucial for organic online retail success. Keywords: Social Commerce, Marketplace Strategy, E-Commerce Analytics, Organic Retail Sales, Supply Chain Marketing